SOCIAL MEDIA AND GEN Z IN SEARCH OF SELF-EXISTENCE AND MENTAL HEALTH - Ranggawani, Bellya (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2025)
Social media has now become an inseparable part of the lives of generation z. Young people for the most part need to show the best version of themselves on social media in order to be accepted and recognized. This study uses a descriptive qualitative approach to explore the relationship between social media users and the search for self-existence and mental health in generation z. Social media has become an inseparable part of generation z's life. The findings of this paper are that this platform provides a space for them to express themselves, build their identity, and connect with others.